Review on Climate Change Impacts and its Adaptation strategies on Food Security in Sub-Saharan Africa - Merertu Berhanu; Alemayehu Oljira Wolde (Socio-Economics/Agribusiness Department, 2019)
Agriculture and food security are key sectors for intervention under climate change and highly sensitive to climate change. In Sub-Saharan Africa, agriculture-the mainstay of rural livelihoods-is particularly vulnerable to the adverse impacts of climate change, and the adaptive capacity of rural smallholders is extremely low. Agricultural Production is highly vulnerable even to low-end predictions for global mean temperatures in 2100, with major implications for rural poverty and for both rural and urban food security. In recent years it has become clear that climate change is an inevitable process. In Sub-Saharan Africa, the expectation is that climate change will have an especially negative impact on agriculture and food security, not only a result of projected warming and rainfall deficits, but also because of the vulnerability of the population. The impact upon agriculture and food security will be of great significance Sub-Saharan Africa. To further investigate the link between climate change, agriculture and food security the realist review method was employed. Analysis of the literature found consistent predictions of decreased crop productivity, land degradation, high market prices, and negative impacts on livelihoods, and increased malnutrition. Adaptation strategies were heavily discussed as a means of mitigating a situation of severe food insecurity across the entire region. This is linked to issues of development, whereby adaptation is essential to counteract the negative impacts and improve the potential of the population to undergo development processes. Findings additionally revealed a gap in the literature about how nutrition will be affected, which is of importance given the links between poor nutrition and lack of productivity.